Sexual Dysfunction in Women Undergoing Fertility Treatment in Iran: Prevalence and Associated Risk Factors - A Bakhtiari; Z Basirat; F Nasiri Amiri (JRI, 2016)
Background: Sexual dysfunctions are one of the most fundamental difficulties for infertile women, which can be as the cause of infertility. This study investigated the prevalence of this disorder and associated factors in order to improve infertility treatment process and the quality of life of women referring to infertility center. Methods: A cross sectional study was performed on 236 women who referred to Fatima Zahra infertility center of Babol, Iran. Data collection tool was a questionnaire contained two parts; demographic characteristics and infertility information. Also, data for sexual dysfunction was obtained through diagnostic interview based on the international classification DSM-IV. For data analysis, logistic and linear regression analysis were used. The p<0.05 was considered significant. Results: Most of women (84.9%) suffered from primary infertility and the mean duration of infertility was 60.2±8.4 months. The prevalence of sexual dysfunction was 55.5% (n=131); including dyspareunia in 28% (n=66), impaired sexual desire and lack of orgasm in 26.3% (n=62 patients), vaginismus in 15.2% (n=36) and lack of sexual stimulation in 13.6% (n=32). Binary logistic regression analysis showed that age, sexual satisfaction and history of mental illness had a significant effect on the probability of experiencing the sexual dysfunction. Conclusion: There is a high prevalence of sexual dysfunction among infertile women. Considering the interaction between sexual dysfunction and infertility, professional health care centers should be sensitive to this effect. Also, more attention must be paid on marital relationships, economic and social situation and infertility characteristics in order to prevent sexual dysfunction development through early screening and psychological interference.